Renal Purge of Hemolymphatic Lipids Prevents the Accumulation of ROS-Induced Inflammatory Oxidized Lipids and Protects Drosophila from Tissue Damage - Li, Xiaoxue; Rommelaere, Samuel; Kondo, Shu; Lemaitre, Bruno (Immunity (Cambridge, Mass.), 2020)
Animals require complex metabolic and physiological adaptations to maintain the function of vital organs in response to environmental stresses and infection. Here, we found that infection or injury in Drosophila induced the excretion of hemolymphatic lipids by Malpighian tubules, the insect kidney. This lipid purge was mediated by a stress-induced lipid-binding protein, Materazzi, which was enriched in Malpighian tubules. Flies lacking materazzi had higher hemolymph concentrations of reactive oxygen species (ROS) and increased lipid peroxidation. These flies also displayed Malpighian tubule dysfunction and were susceptible to infections and environmental stress. Feeding flies with antioxidants rescued the materazzi phenotype, indicating that the main role of Materazzi is to protect the organism from damage caused by stress-induced ROS. Our findings suggest that purging hemolymphatic lipids presents a physiological adaptation to protect host tissues from excessive ROS during immune and stress responses, a process that is likely to apply to other organisms. [Display omitted] •Hemolymphatic lipids are removed by Malpighian tubules after infection and injury•The lipid-binding protein Materazzi removes lipids from the hemolymph•Materazzi prevents hemolymphatic lipid peroxidation and tubule dysfunction•Lipid removal is a stress response that adjusts ROS level and promotes survival Li et al. show that infection or injury in Drosophila induced the excretion of hemolymphatic lipids by Malpighian tubules, the insect kidney, via a mechanism centered on the stress-induced lipid-binding protein, Materazzi. Thus, lipid removal presents a physiological adaptation to protect host tissues from excessive ROS during immune and stress responses, a process that is likely to apply to other organisms.